PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS POWTOON TERHADAP PERENCANAAN KARIER SISWA KELAS XI DI SMA ANGKASA BANDUNG - Nur Fadilah, Septiani Ainun; Hidayat, Wahyu; Masyita Suherman, Maya (IKIP Siliwangi, 2024)
The development of an animated video based on powtoon for the career planning of class XI students at SMA Angkasa Bandung is a new innovation in guidance and counseling service activities in the use of media in it which is very in line with the current developments. Class XI high school students are in the developmental phase of their late teens who already have to think about career choices after graduating from high school. The ability of students to determine their careers is determined by an understanding of future career planning. This study uses research and development methods according to Borg and Gall which aims to produce a product that has been tested for feasibility by several expert validators, namely material experts, media experts, and expert practitioners. The subjects in this study consisted of 10 students in the limited trial, and 30 students in the wide trial, all of whom were class XI students at SMA Angkasa Bandung. Based on the results of the validation test to 3 validators and the results of the limited and extensive trials by students, this animation video based on Powtoon obtained an average percentage result of 95.90%, included in the very suitable category for use through revision. Based on the results of observations and interviews, the responses of teachers and students to this animated video based on Powtoon received a good response and the students had an increased understanding of career planning after conducting guidance and counseling activities using the animated video based on the Powtoon.